Management of Village Fund Distribution to The Community of Lamboya Bawa, Lamboya District, West Sumba Regency - Yohanes Handrianus Laka (IRDH International Journal of Social Sciences & Humanities, 2026)
Lamboya Bawa Village is a village located in Lamboya District, West Sumba Regency. Naturally, the village also manages its village funds. The village finances of Lamboya itself come from several sources: the state budget (APBN), the village's own income (business revenues and rental income from village assets), funds from the province, and funds from the regency. This study uses a descriptive qualitative approach aimed at obtaining a comprehensive and in-depth picture of the process of managing and distributing village fund sources to the community in Lamboya Bawa Village, Lamboya District, West Sumba Regency. Research results and discussion on the Fund Management System in Lamboya Village In managing village funds, a regulation is required that consists of aspects of planning, implementation, administration, reporting, and accountability of village finances. Based on observations and interviews with sources, it was found that the village officials generally understood the management of village finances and prepared financial accountability reports (LPJ) in accordance with the applicable regulations stipulated in the Regulation of the Minister of Home Affairs of the Republic of Indonesia Number 113 of 2014. The Head of Lamboya Village, in preparing the Village Budget (APBDes), must refer to the Village Medium-Term Development Plan (RPJM). With the existence of RPJM, the development carried out by the village government aligns with the results of deliberations, so that development can be on target as planned.